1996
DOI: 10.1038/bjc.1996.122
|View full text |Cite
|
Sign up to set email alerts
|

Cancer incidence near municipal solid waste incinerators in Great Britain

Abstract: Summary By use of the postcoded database held by the Small Area Health Statistics Unit, cancer incidence of over 14 million people living near 72 municipal solid waste incinerators in Great Britain was examined from 1974-86 (England), 1974-84 (Wales) and 1975. Numbers of observed cases were compared with expected numbers calculated from national rates (regionally adjusted) after stratification by a deprivation index based on 1981 census small-area statistics. Observed-expected ratios were tested for decline in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
86
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(91 citation statements)
references
References 27 publications
1
86
0
3
Order By: Relevance
“…The major studies are listed in Table 1, showing that bladder cancer is the most frequently reported malignancy associated with landfills. The detoxifying properties of the liver suggest that environmental toxicants may accumulate in the liver and biliary tract; small excess risks of liver cancer were reported in previous studies around UK incinerators (Elliott et al, 1996(Elliott et al, , 2000. Several studies have shown an association between brain cancer and exposure to pesticides (Bohnen and Kurland, 1995), which are frequently used on landfill sites.…”
mentioning
confidence: 99%
“…The major studies are listed in Table 1, showing that bladder cancer is the most frequently reported malignancy associated with landfills. The detoxifying properties of the liver suggest that environmental toxicants may accumulate in the liver and biliary tract; small excess risks of liver cancer were reported in previous studies around UK incinerators (Elliott et al, 1996(Elliott et al, , 2000. Several studies have shown an association between brain cancer and exposure to pesticides (Bohnen and Kurland, 1995), which are frequently used on landfill sites.…”
mentioning
confidence: 99%
“…Thus we need the confounder distribution within each exposure category, unless z is not a within-area confounder. The requirement for stratumdefined exposure distributions is closely related to mutual standardization as described Often one can attempt to control for confounding via expected numbers E using the regression model: (17,18,22). This approach implicitly assumes, however, that there is no within-area confounding (75).…”
mentioning
confidence: 99%
“…Quite a similar study, in its design and statistical analyses, of health effects related to MSW incineration among general population has been performed in Great Britain, [27][28] where cancer incidence near the MSW incinerators has been investigated.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of such exposure information, even a simple model of decline in risk with distance, equal in all directions, has been used to examine environmental excess risks around putative sources. [23][24][25][27][28] Regarding the blood levels of dioxins around MSW incinerators, the investigator group of Ibaraki prefecture has conducted a well-designed study whose primary purpose is to examine the association of the resident's blood levels of dioxins with the distance from the Shiratori MSW incinerator in Ryugasaki, Ibaraki. 29 At the design stage, 120 residents were selected so as to adjust sex, age, and distance from the incinerator.…”
Section: Discussionmentioning
confidence: 99%